2021
DOI: 10.3390/agronomy11030610
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Different Bunch Cover Materials to Improve Quality of Cavendish Banana Cultivated during Winter and Summer in Thailand

Abstract: Performance of different cover materials on improving Cavendish banana quality was examined during winter and summer. The banana bunch was covered with a thin nonwoven innermost layer, followed by cover materials arranged from inner to outer as follows. (1) Control (commercial cover), paper/polystyrene sheet (PS)/non-perforated blue polyethylene (NPPE), (2) nonwoven (NW)/NPPE, (3) waterproof nonwoven (WPNW), (4) aluminum foil (ALF), and (5) WPNW + ALF. For the summer trial, control without PS layer was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(67 reference statements)
0
2
1
Order By: Relevance
“…This conclusion was made possible by the fact that the same number of hands was kept in the bunches of the two treatments, as well as the same harvesting point was adopted. Chaiwong et al (2021) observed a reduction in the size of the fruit with bagging, a fact that does not seem to have occurred here. Compare to harvest day, brightness of peel of both treatments increase to 35% at the end of storage.…”
Section: No Protectioncontrasting
confidence: 50%
“…This conclusion was made possible by the fact that the same number of hands was kept in the bunches of the two treatments, as well as the same harvesting point was adopted. Chaiwong et al (2021) observed a reduction in the size of the fruit with bagging, a fact that does not seem to have occurred here. Compare to harvest day, brightness of peel of both treatments increase to 35% at the end of storage.…”
Section: No Protectioncontrasting
confidence: 50%
“…The importing demand of Cavendish bananas from Thailand is also increasing. 20 Therefore, in order to be exported to more distant areas, the shelf life of the fruits needs to be extended. The occurring of postharvest diseases such as anthracnose and crown rot during shipping negatively impacts the market value of bananas.…”
Section: Introductionmentioning
confidence: 99%
“…Thailand exports bananas to many countries including China, Japan, Malaysia, Hong Kong, and Cambodia. The importing demand of Cavendish bananas from Thailand is also increasing 20 . Therefore, in order to be exported to more distant areas, the shelf life of the fruits needs to be extended.…”
Section: Introductionmentioning
confidence: 99%